Permanent draft genome sequence of Comamonas testosteroni KF-1. Issue 2 (March 2013) - Weiss, Michael; Kesberg, Anna; LaButti, Kurt; Pitluck, Sam; Bruce, David; Hauser, Loren; Copeland, Alex; Woyke, Tanja; Lowry, Stephen; Lucas, Susan; Land, Miriam; Goodwin, Lynne; et al.
Abstract Comamonas testosteroni KF-1 is a model organism for the elucidation of the novel biochemical degradation pathways for xenobiotic 4-sulfophenylcarboxylates (SPC) formed during biodegradation of synthetic 4-sulfophenylalkane surfactants (linear alkylbenzenesulfonates, LAS) by bacterial communities. Here we describe the features of this organism, together with the complete genome sequence and annotation. The 6, 026, 527 bp long chromosome (one sequencing gap) exhibits an average G+C content of 61.79% and is predicted to encode 5, 492 protein-coding genes and 114 RNA genes.